Correlation Study of The Number of Cloud to Ground Lightning Strikes With Rainfall in The City of Pontianak - Pujianda, Tegar; A. Gani, Usman; Danial, Danial (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2024)
Research has been conducted on lightning strikes with rainfall to determine the relationship between the two. The problem in this study is how the relationship between lightning clouds to the ground with rainfall in Pontianak City. The lightning data used is lightning detector data originating from the BMKG Supadio Station and rainfall on the BMKG website. The method used in this study performed a linear regression test and a correlation test using the Spearman correlation method. The results obtained show a relationship between rainfall and cloud lightning to the ground daily with a Spearman correlation of 0.2237 which means that the relationship between the two variables has weak strength. The strength of the relationship between the number of cloud lightning strikes to the ground with low rain intensity and the 22.37% relationship between rainfall intensity and the number of cloud lightning to the ground. The correlation coefficient obtained is positive. The relationship between the two variables is unidirectional and can be interpreted that high rain intensity will cause the number of lightning strikes to increase. The intensity of rainfall determines less the size of the number of cloud lightning strikes to the ground. The correlation value between the number of cloud lightning strikes to the ground and the intensity of rainfall in Pontianak City in the weak correlation category with a small value (R2) close to zero. The coefficient of determination is 0.088. This means that 8.8% of the variation from lightning strikes can be explained by variable variations in rainfall.